Deploying SMS Gateway in the Design and Development of Web and Mobile Academic Information Systems using the Waterfall Method - Al Fansyah, Fajar; Widodo, Tri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
: The integration of technology in various sectors, beyond its common application in the gaming industry, has extended to the field of education. This evolution mandates parallel progress in academic institutions to keep pace with technological developments. A significant challenge identified was the reliance on manual accounting methods at SMAN 1 Kejobong, which includes teacher management, staff, and assistant administration, as well as processing student learning data. Outdated practices often lead to inaccuracies and inefficiencies, resulting in time-consuming data collection and potential losses for all stakeholders. To overcome this problem, it is proposed to implement a comprehensive information system or e-learning platform. However, the implementation of e-learning in educational institutions often encounters obstacles due to user discomfort or incompatibility with the institution's needs. This study validated all system features through Black box Testing and user satisfaction assessments, resulting in an average satisfaction level of 73.7%. The expected outcome is increased efficiency and accuracy in academic processes and student management, thereby facilitating a more effective learning and teaching environment.